Stent retriever placement in embolectomy: the choice of the post-bifurcational trunk influences the first-pass reperfusion result in M1 occlusions. (27th July 2018) - Maus, Volker; Brehm, Alex; Tsogkas, Ioannis; Henkel, Silja; Psychogios, Marios-Nikos
Abstract : Background: Embolectomy using Stent retriever Assisted Vacuum-locked Extraction (SAVE) is effective in intracranial large vessel occlusion. Which post-bifurcational trunk should be chosen for distal stent retriever placement in M1 occlusions is, however, elusive. Methods: We conducted a retrospective analysis of prospectively collected data from a comprehensive stroke center between 2015 and 2017. Eighty-nine consecutive patients with M1 occlusions were treated with SAVE. Digital subtraction angiography (DSA) series were studied to determine the anatomy of middle cerebral artery division, the position of the stent retriever, and to measure vessel diameters. The primary endpoint was first-pass complete/near-complete reperfusion, defined as a modified Thrombolysis in Cerebral Infarction (mTICI) score of 2c or 3, after distal stent retriever placement in the inferior trunk. Results: In 76/89 (85%) patients, microcatheter series were documented. A microcatheter was placed within the inferior trunk in 30/76 (40%) cases. First-pass near-complete/complete reperfusion was more likely to be achieved when the inferior trunk was used for stent retriever placement rather than the superior trunk (mTICI ≥2c: 22/30 (73%) vs 22/46 (48%), P=0.034; and mTICI 3: 20/30 (67%) vs 17/46 (37%), P=0.018). Median diameter of the inferior trunk was larger than the superior trunk (1.4 mm (IQR 1.26–1.62) vs 1.18 mm (IQR 0.98–1.43), P=0.011). The inferior trunk was dominant in 56/76 (74%) cases. Successful reperfusion was associated with placement within the dominant trunk (33/40 (83%) vs 22/36 (61%), P=0.044). Conclusion: The choice of the inferior trunk for distal stent retriever placement in M1 occlusions is associated with a high rate of first-pass near-complete/complete reperfusion when using SAVE.